Exploiting wastes in concrete proceedings of the international seminar held at the University of Dundee, Scotland, UK on 7 September 1999 - Dhir, Ravindra K.; Jappy, Trevor G. (Thomas Telford, 1999)
Topics covered in 'Exploiting Wastes in Concrete' include maximising the use of waste materials in concrete production and the use of alternative materials in concrete.